The effect of dietary treatment on the progression of chronic renal failure, renal osteodystrophy and uraemic neuropathy, and on the nutritional status of uraemic patients - Herselman, M. G.(Martha Gertruida) (Stellenbosch : Stellenbosch University, 2012)
One copy microfiche.